2015
DOI: 10.1007/s10585-015-9709-2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary soy isoflavones increase metastasis to lungs in an experimental model of breast cancer with bone micro-tumors

Abstract: Bone is one of the most common sites for metastasis in breast cancer (BC). Micro-metastasis in bone marrow was detected in 30% of patients with stage I, II, or III BC at primary surgery and is a strong indicator of poor prognosis. The role dietary soy isoflavones play in BC with bone micro-metastasis is unclear. In this study, we examined the effects of genistein, daidzein, (−)-equol or a mixture of soy isoflavones on BC with bone micro-metastasis using an experimental model of murine mammary cancer 4T1 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 41 publications
0
39
1
1
Order By: Relevance
“…Furthermore, the co-treatment of HeLa cells with 7and MRP2)[94]. Nevertheless, the effect of isoflavones on cancer remains controversial, as a recent study has shown that dietary soy isoflavones, including genistein, daidzein and (-)-equol, increased the formation of metastatic tumor nodules in lungs using an in vivo murine model of breast cancer with bone breast 4T1 cells micro-metastases[95].…”
mentioning
confidence: 99%
“…Furthermore, the co-treatment of HeLa cells with 7and MRP2)[94]. Nevertheless, the effect of isoflavones on cancer remains controversial, as a recent study has shown that dietary soy isoflavones, including genistein, daidzein and (-)-equol, increased the formation of metastatic tumor nodules in lungs using an in vivo murine model of breast cancer with bone breast 4T1 cells micro-metastases[95].…”
mentioning
confidence: 99%
“…There is some evidence that shows soy isoflavones such as daidzein can enhance cancer characteristics in mouse mammary tumor cell lines (Koo et al, ; Yang et al, ). In addition, in vivo studies also point to the possibility that soy isolfavones might interfere with the therapeutic effect of tamoxifen (Du et al, ).…”
Section: Dietary Sources Of Phytoestrogens Known To Affect Breast Patmentioning
confidence: 99%
“…Genisztein esetében 28%, daidzein esetében 35,9%, equolos csoportnál 28,6%, több izoflavonoiddal együtt kezelt egyedeknél ez az érték pedig 34,3% volt. A kísér-let tehát a fitoösztrogének metasztázisképzést fokozó hatását bizonyította, ennek alapján is felvetődik a gondolat, hogy rákban szenvedőknél kockázattal járhat fogyasztásuk [37].…”
Section: öSszefoglaló Közleményunclassified